Ambrisentan for the treatment of pulmonary arterial hypertension - Brian Casserly; James R Klinger (Drug Design, Development and Therapy, 2008)
Brian Casserly1,3, James R Klinger2,31Division of Pulmonary Medicine, The Memorial Hospital of Rhode Island, Pawtucket, RI, USA; 2Division of Pulmonary Sleep and Critical Care Medicine, Rhode Island Hospital; 3Waren Alpert Medical School of Brown University, Providence, RI, USAAbstract: Ambrisentan is an endothelin receptor antagonist (ERA) that was recently approved for treatment of pulmonary arterial hypertension (PAH). Endothelin (ET) is a potent vasoconstrictor with mitogenic, hypertrophic and pro-inflammatory properties that is upregulated in pulmonary hypertensive diseases. The biologic effects of ET are mediated by 2 cell surface receptors termed ETA and ETB. ETA mediates the vasoconstrictor effect of ET on vascular smooth muscle, whereas ETB is expressed primarily on vascular endothelial cells where it induces nitric oxide synthesis and acts to clear ET from the circulation. Ambrisentan is the first ETA selective ERA approved for use in the US. Recently published clinical trials in patients with PAH demonstrate improvement in functional capacity and pulmonary hemodynamics similar to other ETA selective and non-selective ERAs. Its once daily dosing and lower incidence of serum aminotransferase elevation offer potential advantages over other ERAs, but further experience with this agent is needed to fully understand its long-term efficacy and safety. This review discusses the endothelin family of proteins and receptors and their role in the pathophysiology of pulmonary hypertensive diseases. It also examines the development process, safety profile and clinical trials that have resulted in ambrisentan being approved for treatment of PAH.Keywords: ambrisentan, endothelin receptor antagonist, pulmonary hypertension, endothelin